xEV Simulator Virtual Prototyping of Electrified Vehicles Using Real Data - Kauppinen, Kristoffer; Lingnert, Oskar (My University, 2013)
One way of reducing the emissions in the vehicle industry is to use electrified vehicles. An important method when developing new vehicles is to use simulations. In this thesis the possibility of developing a simulation tool that uses real log data as input, to anticipate the energy consumption of an identical vehicle body as the logged one but with a modeled electric powertrain, is investigated. Logged data of an electric and a conventional vehicle are analyzed to understand which signals are needed and how these signals are either measured or calculated. Further the signals are used to calculate the external forces that acts on the vehicle. The estimated external forces are used as inputs to the simulation tool to enable simulation. The results have shown that it is possible to calculate the external forces that acts on a logged vehicle during motion. When comparing the external forces for a specified route, driven with different versions of the same vehicle body but with different powertrains, it shows that the forces are approximately the same, which indicates that the method works. The simulation results show that the variations in the results are within 5% when verifying the log data from an electric vehicle with a simulated electric powertrain consisting of the same powertrain components. The developed simulation tool can be used to simulate an electrical powertrain, with input parameters based on a logged conventional vehicle.
Keywords: Elkraftteknik; Electric power engineering